2005
DOI: 10.1242/jeb.01759
|View full text |Cite
|
Sign up to set email alerts
|

Influence of host size on the clutch size and developmental success of the gregarious ectoparasitoid Eulophus pennicornis (Nees)(Hymenoptera: Braconidae) attacking larvae of the tomato moth Lacanobia oleracea (L.) (Lepidoptera: Noctuidae)

Abstract: SUMMARY The relationship between clutch size, host size and progeny survival in the gregarious ectoparasitoid Eulophus pennicornis was investigated in a number of scenarios. When naive parasitoids were exposed singly to Lacanobia oleracea hosts, clutch size was strongly correlated with the size of the host. However, survival of parasitoid offspring was negatively affected by the size of the host such that, in larger hosts, greater wasp larval and pupal mortality was recorded. As a result, no gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
(64 reference statements)
1
23
0
Order By: Relevance
“…Previous work [8,14] has shown that early sixth stadium hosts (0 -48 h post ecdysis) are preferentially parasitized by E. pennicornis and suggest that juvenilization, and the capacity to induce it, have been selective drivers in this parasitoid preferentially parasitizing hosts of this age. The powerful juvenilizing effect that a component of E. pennicornis's venom induces in the host lends credence to the fact that it is probably critical for the wasp to ensure that hosts do not become physiologically committed to pupation once they have been parasitized.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous work [8,14] has shown that early sixth stadium hosts (0 -48 h post ecdysis) are preferentially parasitized by E. pennicornis and suggest that juvenilization, and the capacity to induce it, have been selective drivers in this parasitoid preferentially parasitizing hosts of this age. The powerful juvenilizing effect that a component of E. pennicornis's venom induces in the host lends credence to the fact that it is probably critical for the wasp to ensure that hosts do not become physiologically committed to pupation once they have been parasitized.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the observable effects of venom factors on various aspects of host development have not been reported in any detail, particularly with respect to injection into different host stages, and the response of larvae to different doses. These points are of particular relevance as E. pennicornis has the ability to parasitize a range of stages of L. oleracea (fourth, fifth and sixth stadium larvae) and to vary its clutch precisely in proportion to the size of the host [14]. Furthermore, the reproductive success of this parasitoid appears linked to both its ability to identify the highest quality hosts and to successfully regulate their development [8,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies conclude that clutch size increases with host size. Host size is in many instances a good predictor of nutritional quality of the host (Bell et al 2005;Hardy et al 1992;Klein et al 1991;Zaviezo and Mills 2000); however, there are exceptions where parasitoids rely not simply on host size to assess nutritional quality (Dorn and Beckage 2007;Hackermann et al 2007). These studies support the above expectations that superparasitism should be a more frequent event in the field when fewer but larger hosts are available (Gu et al 2003).…”
Section: Discussionmentioning
confidence: 99%